Deterministic and stochastic dynamic study on inelastic structures with force analogy method - Wang, Zhe (2008)
In this research, the force analogy method is used as a main tool to analyze the inelastic dynamic response and energy dissipation of structures in both deterministic and stochastic fields. A simple analytical method of modeling the panel zone deformation is proposed. The model of rigid end offsets is also included to give a more accurate structural model. Based on the proposed model, numerical simulations performed on different models shows that rigid end offsets as well as elastic and inelastic deformation of panel zones have significant effects on dynamic behavior of inelastic structures subjected to earthquake excitation. The same conclusions also can be drawn from the statistic results obtained by the Monte Carlo simulation method.